A Look at the 'Culture-Communication Relation' and 'Intercultural Communication' Theories - Altay, Recep; Kavuran, Tamer (Bolu Abant İzzet Baysal Üniversitesi, 2022)
Today, when the world has become a global village, the expectations of people with different cultural characteristics to live in harmony have made culture and communication inseparable. ‘Language’, which is a symbol representing the common codes of culture and communication, is also a defining element of culture. In a culture where the reproduction and sharing of meaning is very important, language based on verbal expressions is at the foreground. This situation reveals the relationship between communication and culture. While the cultural infrastructure gained through communication allows the development of new technologies, advances in the field of communication accelerated the change of the cultural superstructure. The efforts of people to come together to understand and communicate with each other have revealed intercultural communication. The need to determine the level of communication competence in cultural encounters has paved the way for intercultural communication to be considered as an interdisciplinary field. In order to base this cultural structure on a scientific basis, a need for theoretical perspectives has arisen. In this compilation study, the relationship between culture-communication concepts is discussed and cultural encounters of individuals are explained with intercultural communication theories.

Dünyanın küresel bir köy haline geldiği günümüzde farklı kültürel özelliklere sahip insanların uyum içerisinde yaşama beklentileri, kültür ve iletişimi ayrılmaz kılmıştır. Kültür ve iletişimin ortak kodlarını temsil eden bir sembol olan dil, aynı zamanda kültürün bir tanımlayıcı unsurudur. Anlamın yeniden üretilmesinin ve paylaşılmasının çok önemli olduğu kültürde, sözel ifadelere bağlı dil ön plandadır. Bu durum iletişim ile kültürün ilintisini ortaya koymaktadır. İletişim vasıtasıyla kazanılan kültürel alt yapı, yeni teknolojilerin gelişimine olanak sağlarken iletişim alanındaki ilerlemeler kültürel üst yapının değişimini hızlandırmıştır. İnsanların bir araya gelerek birbirlerini anlama ve iletişim kurma çabaları kültürlerarası iletişimi ortaya çıkarmıştır. Kültürel karşılaşmalarda iletişim yeterliğinin düzeyini belirleme ihtiyacı, kültürlerarası iletişimin disiplinlerarası bir alan olarak ele alınmasına zemin hazırlamıştır. Bu kültürel yapıyı bilimsel bir temele dayandırmak için kuramsal perspektiflere ihtiyaç doğmuştur. Bu derleme çalışmasında, kültür-iletişim kavramları arasındaki ilişki ele alınmış, bireylerin kültürel karşılaşmaları kültürlerarası iletişim kuramlarıyla açıklanmıştır.
Kültür-İletişim İlintisi ve Kuramsal Yaklaşımlara Bir Bakış
Keywords: Communication and Media Studies; İletişim ve Medya Çalışmaları